Seal apikal dari sealer berbahan dasar resin epoksi dan berbahan dasar mineral trioxideaggregate (Apicalsealingofepoxyresin-basedandmineral trioxideaggregatebased root canal sealers) - Munirah Munirah; Aries Chandra Trilaksana; Juni Jekti Nugroho (Journal of Dentomaxillofacial Science, 2014)
This study aimed to compare the apical sealing of epoxy resin-based and mineral trioxide aggregate (MTA)-based rootcanal sealer. Twenty four permanent central incisors were selected at random and divided into 4 groups (N = 24),namely positive control group, negative control group, Fillapex obturator group (MTA, and TopSeal group (epoxyresin). The samples were decoronated, root canal preparation, then kept in incubator of 37 C for 24 hours. Sampleswere immersed in india ink for 7 days. The samples were washed with distilled water, dried and nail varnish removed.The samples was grooved longitudinally on both side, and then carefully sectioned. Penetration was measured using astereo microscope and given score 0-4. Measurements were analyzed statistically. By using the Mann Whitney andKolmogorov-Smirnov tests, there is no significant difference between the apical sealing of the epoxy resin root canalsealer with MTA root canal sealer based (p>0.05). It means that the apical sealing of the epoxy resin root canal sealerbased comparable with MTA root canal sealer based. It was concluded that the apical sealing of epoxy resin-based sealer does not different to the MTA-based sealer.